Indirect co‐culture of islet cells in 3D biocompatible collagen/laminin scaffold with angiomiRs transfected mesenchymal stem cells. (23rd February 2023) - Sabet Sarvestani, Fatemeh; Tamaddon, Ali‐Mohammad; Yaghoobi, Ramin; Geramizadeh, Bita; Abolmaali, Samira Sadat; Kaviani, Maryam; Keshtkar, Somayeh; Pakbaz, Sara; Azarpira, Negar
Abstract: Diabetes is an autoimmune disease in which the pancreatic islets produce insufficient insulin. One of the treatment strategies is islet isolation, which may damage these cells as they lack vasculature. Biocompatible scaffolds are one of the efficient techniques for dealing with this issue. The current study is aimed to determine the effect of transfected BM‐MSCS with angiomiR‐126 and ‐210 on the survival and functionality of islets loaded into a 3D scaffold via laminin (LMN). AngiomiRs/Poly Ethylenimine polyplexes were transfected into bone marrow‐mesenchymal stem cells (BM‐MSCs), followed by 3‐day indirect co‐culturing with islets laden in collagen (Col)‐based hydrogel scaffolds containing LMN. Islet proliferation and viability were significantly increased in LMN‐containing scaffolds, particularly in the miRNA‐126 treated group. Insulin gene expression was superior in Col scaffolds, especially, in the BM‐MSCs/miRNA‐126 treated group. VEGF was upregulated in the LMN‐containing scaffolds in both miRNA‐treated groups, specifically in the miRNA‐210, leading to VEGF secretion. MiRNAs' target genes showed no downregulation in LMN‐free scaffolds; while a drastic downregulation was seen in the LMN‐containing scaffolds. The highest insulin secretion was recorded in the Oxidized dextran (Odex)/Col LMN+ group with miRNA‐126. LMN‐containing biocompatible scaffolds, once combined with angiomiRs and their downstream effectors, promote islets survival and restore function, leading to enhanced angiogenesis and glycemic status. Significance statement: This study investigated the synergy effect of LMN and angiomiRs on islet cells. It was shown that LMN‐containing scaffolds, once combined with miRNAs‐126 and ‐210 might help islets survive and restore function, thereby enhancing angiogenesis and glycemic status. These data could help to improve islets transplantation state in diabetic conditions.